Nonovershooting multivariable tracking control for time-varying references - Schmid, R.; Ntogramatzidis, Lorenzo; Gao, Suzhan (IEEE, 2013)
We consider the classic problem of exact output regulation for a linear time invariant plant. Under the assumption that a state feedback output regulator exists, we adapt the design methods of Schmid and Ntogramatzidis [1] to obtain a regulator that will track a time-varying reference without overshoot in the transient response.